Religious tolerance in Maturudy’s world-view (Journal of Philosophy Culture and Political Science, 2016)
Imam Abu Mansur al-Maturidi resting upon the power of uahy and reason succeeded in shaping his systematic religious perception. It is obvious that in the process of converting into Islam they were influenced by their old religious ideas, besides, the new muslim turkic tribes were able to cling their old national self-determination. During this Islamization process Turkic tribes adopted Hanafy – Maturidi mazhab. Particularly, the narrow spread of this mazhab promoted it to be identified as specifically Turkic mazhab.In this article we attempted to view the tolerant principle by Maturidi towards the other faiths based on his own works and the modern researched works.
Keywords: Maturidi; religion; mazhab; tolerance